Effective Marketing Strategies of McDonald’s in Malaysia and Indonesia - Oh Zi Jian; A.A. Gde Satia Utama; Wan Nurin Afrina Binti Wan Musa; Wafiq Bin Hasly; Ramizah Fatimah Binti Al-Rifae; Nur Syawaltul Aisyah Binti Mohamad Hussa; Nofel Andriawan (AIBPM Publisher, 2021)
The purpose of this study is to examine the effective marketing strategies of McDonald’s in Malaysia and Indonesia. The research method used online survey and analyzed by using SPSS version 24. Literature reviews, journals, and papers also are analyzed to support the collected data. The findings indicated that 87.07% of respondents are satisfied with the existing services whereas 69.83% of respondents are satisfied with the food by McDonald's. The findings also showed that the majority of consumers knew McDonald's from social media. The findings provide suggestions for future research and improvement provided by McDonald especially for offering more options and providing more discounts in their services.